Targeted lung denervation modulates the mucosal epithelial transcriptome in COPD. Issue 4 (27th December 2022) - Srikanthan, Karthi; Kistemaker, Loes; Slebos, Dirk-Jan; Gesierich, Wolfgang; Darwiche, Kaid; Bonta, Peter; Deslee, Gaetan; Shah, Pallav; Gosens, Reinoud
Targeted lung denervation (TLD) is a novel treatment for COPD with evidence of a potential beneficial effect on exacerbation frequency [1]. It is a minimally invasive procedure involving the ablation of the airway nerve trunks of the vagus nerve that travel parallel to and outside the main bronchi, thereby reducing neuronal acetylcholine release. It has been postulated that TLD may share a similar mechanism of action with the inhaled long-acting muscarinic antagonists [2]. This study shows that TLD reduces airway epithelial expression of genes related to acetylcholine processing and airway inflammation, which may help to elucidate the mechanism for its effect of reducing severe exacerbations in COPD https://bit.ly/3dWcqZk